2003
DOI: 10.1590/s0100-879x2003001000022
|View full text |Cite
|
Sign up to set email alerts
|

Infrared coagulation versus rubber band ligation in early stage hemorrhoids

Abstract: The ideal therapy for early stages of hemorrhoids is always debated. Some are more effective but are more painful, others are less painful but their efficacy is also lower. Thus, comfort or efficacy is a major concern. In the present randomized study, a comparison is made between infrared coagulation and rubber band ligation in terms of effectiveness and discomfort. One hundred patients with second degree bleeding piles were randomized prospectively to either rubber band ligation (N = 54) or infrared coagulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
(16 reference statements)
2
35
0
Order By: Relevance
“…Dimitroulopoulos in a RCT reported 48.7% of postoperative pain; in Gupta's RCT 100% of patient complained pain (32,34). In contrast, Ahmad reported only 16% of pain rates (35).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Dimitroulopoulos in a RCT reported 48.7% of postoperative pain; in Gupta's RCT 100% of patient complained pain (32,34). In contrast, Ahmad reported only 16% of pain rates (35).…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, Ahmad reported only 16% of pain rates (35). Post-operative bleeding ranged from 44% in Dimitroulopoulos' to 15% in Gupta's RCTs (32,34). We evaluated the effectiveness in bleeding and prolapses control for different degrees of hemorrhoids; results are shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 5-year follow-up study on patients who had undergone IRC, 18 since this method is quick, safe, effective and painless for treatment of hemorrhoids, the conventional method can be changed to this method as an alternative method. In a study by Gupta 19 comparing IRC and rubber band ligation, it was shown that IRC is preferred to ligation in regard to lower postoperative pain as well as more suitable in case of recurrence. Charúa Guindic et al 20 introduced IRC technique as an excellent treatment method for hemorrhoids grades I and II with considerable low postoperative pain, low cost, and high success rate, with its failure rate estimated to be only 6.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pain and anal discomfort were reported to be greater when multiple bandings were performed. Gupta [23] found that out of 44 patients that underwent RBL, seven patients (15.9 %) reported pain. Ayman et al [4] found pain in 31 patients (4.13 %) out of the 750 studied group.…”
Section: Discussionmentioning
confidence: 99%